PENGARUH CURRENT RATIO EARNING PER SHARE DAN RETURN ON ASSET PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Chaya, Wahid Nur; Prima, Argo Putra (SCIENTIA JOURNAL, 2019)
Information about the financial conditions and results of the business activities is very useful for the different parties that are also outside the company. Useful information, such as the company's ability to pay short-term debts, the company's ability to pay interest and capital loans, and the company's success in increasing the amount of capital. When evaluating the financial performance of a company, it is possible to use a certain size or benchmark. The profitability analysis can be used as a benchmark to assess the financial performance of the company. Return on capital (ROA). The purpose of this study was to determine how much influence the current report had, the earnings per share and the debt / equity ratio on the return on assets in production companies listed on the Indonesian stock exchange in 2014-2018. The technique used in this study is to sample students with criteria that meet the requirements and have obtained 8 production companies that were involved in the data in a 5-year period to obtain 40 samples. The results of this study show that the variable earnings per share has a significant effect on the ROA, while the variables Current Ratio and Debt / Capital Ratio have no effect on the ROA. The results of the analysis show at the same time that the current variables Ratio, Earnings per share and Debt / capital ratio have a significant effect on the performance of assets.